Synthesis of Zr2WP2O12/ZrO2 Composites with Adjustable Thermal Expansion - Zhang, Zhiping; Sun, Weikang; Liu, Hongfei; Xie, Guanhua; Chen, Xiaobing; Zeng, Xianghua (Frontiers in Chemistry, 2017)
Zr2WP2O12/ZrO2 composites were fabricated by solid state reaction with the goal of tailoring the thermal expansion coefficient. XRD, SEM and TMA were used to investigate the composition, microstructure and thermal expansion behavior of Zr2WP2O12/ZrO2 composites with different mass ratio. Relative densities of all the resulting Zr2WP2O12/ZrO2 samples were also tested by Archimedes’ methods. The obtained Zr2WP2O12/ZrO2 composites were comprised of orthorhombic Zr2WP2O12 and monoclinic ZrO2. As the increase of the Zr2WP2O12, the relative densities of Zr2WP2O12/ZrO2 ceramic composites increased gradually. The coefficient of thermal expansion of the Zr2WP2O12/ZrO2 composites can be tailored from 4.1×10-6 K-1 to -3.3×10-6 K-1 by changing the content of Zr2WP2O12. The 2:1 Zr2WP2O12/ZrO2 specimen shows close to zero thermal expansion from 25 °C to 700 °C with an average linear thermal expansion coefficient of -0.09×10-6 K-1. These adjustable and near zero expansion ceramic composites will have great potential application in many fields.